Modern Museum Communications as a Means of Visitors Attracting - Pavlovskaya, Olga; Karipidi, Alla; Baturyan, Margarita; Sakhno, Olga; Borisova, Uliana (International Journal of Criminology and Sociology, 2022)
The purpose of the study is to analyze the websites of museums in Russia in the European context. The Fine Arts museums in five regional centers of Russia and European Union, namely, in France, Germany, Poland, Croatia, and Lithuania were chosen for the assessment of their websites by four criteria: design, content, usability, and dynamism. A rating of the target Russian museum websites was compiled based on a comparative analysis of their compliance with these criteria. The findings allow concluding that some of the web resources of Russian regional museums meet the European standards, which let them powerfully join the modern virtual space and win both Russian and foreign audiences. The scienсe-based approach to a single virtual cultural space, which is currently on the focus of the museum institutions, supports the assumption of the museum websites to be a potent tool for the art communication with society. The practical value of the study is determined by possible uses of the results in streamlining and upgrading the museum sites, as well as in courses and training programs on museology, management, and marketing of social and cultural activities.